THE MYTH OF “THE EARLIER THE BETTER” IN FOREIGN LANGUAGE LEARNING OR THE OPTIMAL AGE TO LEARN A FOREIGN LANGUAGE - Tuyet, Tran Thi (VNU Journal of Foreign Studies; Vol 36 No 1, 2020)
A widespread belief of ‘the earlier the better’ in foreign language learning has led to generous investment from both families and societies on young children’s foreign language learning. Nonetheless, the outcome of such investment is often under expectation. This article aims to discuss if there is an optimal age to learn a foreign language. By putting together both related theoretical and empirical research in the international literature, this article forwards the message that the general belief of ‘the earlier the better’ in foreign language learning is often misleading, and too early investment in children’s foreign language learning may become a big waste. Ultimately, the key factor in effective foreign language teaching and learning is how to adapt the teaching style to match the learning style of students rather than when to let children start learning a foreign language.